2022
DOI: 10.3390/dj10060101
|View full text |Cite
|
Sign up to set email alerts
|

Early Response and Clinical Efficacy of a Mouthwash Containing Chlorhexidine, Anti Discoloration System, Polyvinylpyrrolidone/Vinyl Acetate and Sodium DNA in Periodontitis Model: A Triple-Blind Randomized Controlled Clinical Trial

Abstract: Polyvinylpyrrolidone/vinyl acetate (PVP/VA) is a molecule with increased adhesion capacity, and can be associated in the bacterial plaque control with sodium DNA, a natural anti-aging molecule able to improve gingival trophism. The aim of the study is to test at two weeks the antimicrobial and antiplaque properties, subjects affected by chronic periodontitis, showed by a mouthwash containing Chlorhexidine (CHX) 0.2% with Anti Discoloration System (ADS), PVP-VA, and Sodium DNA in comparison with a placebo mouth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Finally, in addition to the mechanical removal of the plaque through SRP, natural compound and photodynamic approaches have been tested in RA patients as adjuvant treatments [146][147][148]. Curcumin, the biologically active part of the Curcuma longa root, belongs to the phenolic compound group and has demonstrated antioxidant and anti-bacterial properties.…”
Section: The Effect Of Non-surgical Periodontal Treatment (Nspt) On R...mentioning
confidence: 99%
“…Finally, in addition to the mechanical removal of the plaque through SRP, natural compound and photodynamic approaches have been tested in RA patients as adjuvant treatments [146][147][148]. Curcumin, the biologically active part of the Curcuma longa root, belongs to the phenolic compound group and has demonstrated antioxidant and anti-bacterial properties.…”
Section: The Effect Of Non-surgical Periodontal Treatment (Nspt) On R...mentioning
confidence: 99%
“…Antibodies response with mRNA-1273 vaccine persisted 180 days after the second dose, as identified by three distinct serologic assays [ 327 ]. In one study, an antibody reduction of 37.9% was observed in seronegative persons and 44.7% in seropositive subjects compared to the highest antibody titer [ 328 , 329 , 330 , 331 , 332 , 333 , 334 , 335 , 336 , 337 ]. In an important study, it was shown that 30% of the vaccinated elderly did not reach the antibody response after the second dose.…”
Section: Side Effects and Post-vaccination Pathologies Related To Ant...mentioning
confidence: 99%
“…Biofilm formation is an important marker for increasing the severity of periodontal disease, which develops as dental plaque enhances the severity of antibiotic tolerance and treatment difficulties through its adhesion and biofilm development on medical devices, which can result in serious illness [ 21 ]. The traditional treatment of these diseases involves the mechanical removal of dental plaque, antibiotics, and chemical agents such as chlorhexidine [ 8 , 9 , 22 , 23 , 24 ]. These treatments may produce many side effects including pain, swelling, tooth sensitivity, drug resistance, and tooth discoloration [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional treatment of these diseases involves the mechanical removal of dental plaque, antibiotics, and chemical agents such as chlorhexidine [ 8 , 9 , 22 , 23 , 24 ]. These treatments may produce many side effects including pain, swelling, tooth sensitivity, drug resistance, and tooth discoloration [ 22 , 23 , 24 , 25 ]. Consequently, current strategies using naturally beneficial bacteria groups such as probiotics are highly desirable for balancing the oral bacterial community, reducing oral pathogens, and stimulating the host’s immune responses [ 7 , 23 , 26 , 27 , 28 ] that may decrease the severity of oral disease and prevent oral pathogen sustainably, which is similar to the immunomodulatory substance.…”
Section: Introductionmentioning
confidence: 99%